(untitled) (Palíndromo, 2020)
This article is based on the project "Urban ornament: an inventory of ornamental grids in Belo Horizonte (and other beauties)", which resulted in the author’s doctoral thesis and in a book with the same name, which has as its outcome an exhaustive inventory of vector drawings that reproduce models of artistic metalwork integrated with architecture in the capital of Minas Gerais/Brazil. The objective is to circumscribe, as an object of analysis, the recurring architectural typol-ogies found in the fieldwork, named here patchwork houses. These houses that combine tiles and ornamental grids on their façades, as well as the interviews we conducted with their residents are, here, a pretext to reflect about the survival of the ornament in the current urban space, based on its popular dimension, the urban narratives and the relationship between imagination and memory.